Brazil's Fiscal Stance during 1995-2005 The Effect of Indebtedness on Fiscal Policy Over the Business Cycle - de Mello, Luiz (OECD Publishing, 2006)
Brazil's fiscal adjustment since the floating of the real in 1999 has been impressive, even in periods of lacklustre growth. This suggests a remarkable fiscal effort to ensure public debt sustainability. To better gauge the magnitude of this adjustment effort, this paper applies the methodology used by the OECD Secretariat to distinguish changes in the fiscal stance that are due to policy action from those that are related to the automatic stabilisers built into the tax code, the social security system and unemployment insurance. The paper's main finding is that discretionary action tends to be essentially pro-cyclical in downturns, underscoring the presence of a strong "sustainability motive" in the conduct of Brazilian fiscal policy. Spending on mandatory items, such as personnel, are pro-cyclical in upturns too, which can create a "ratcheting-up" effect on government spending over time, an issue that will have to be addressed to improve the quality of on-going fiscal adjustment. An increase in the debt-to-GDP ratio by 1 percentage point is associated with a decrease in discretionary federal spending by 0.33 percentage point during 1997-2005. This responsiveness appears to have become stronger after the floating of the real in 1999. This Working Paper relates to the 2005 OECD Economic Survey of Brazil (www.oecd.org/eco/survey/brazil)
Keywords: Economics; Brazil